The Ability of Students’ Scientific Argumentation of Acid-Base and Buffer Solution through Science Writing Heuristic (SWH) - R Arizal Firmansyah; Linda Hesti Kumala (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2018)
AbstractMany students have found the difficulties to give proper evidence scientifically. Therefore, it is necessary to provide the learning approach model which guides students to argue scientifically on the laboratory work writing namely science writing heuristic (SWH). In this research, we tried to describe the quality of students scientific argumentation on acid-base and buffer solution laboratory work writing through mixed methods embedded concurrent. The research data was obtained through assessment rubric of ability scientific argumentation SWH formatted and field notes. The overall of ability scientific argumentation was moderate (63.60%). From this research, we found that laboratory work writing with laboratory report SWH formatted can improve students’ ability on their scientific argumentation.AbstrakBanyak pelajar telah menemukan kesulitan untuk memberikan bukti yang tepat secara ilmiah. Oleh karena itu, perlu untuk menyediakan model pendekatan pembelajaran yang memandu pelajar untuk berdebat secara ilmiah tentang penulisan kerja laboratorium yaitu heuristik penulisan sains (SWH). Dalam penelitian ini, kami mencoba mendeskripsikan kualitas argumentasi ilmiah pelajar pada penulisan kerja laboratorium larutan asam-basa dan buffer melalui metode campuran yang disatukan secara bersamaan. Data penelitian diperoleh melalui rubrik penilaian kemampuan argumentasi ilmiah SWH yang diformat dan catatan lapangan. Keseluruhan argumentasi ilmiah kemampuan adalah sedang (63,60%). Dari penelitian ini, kami menemukan bahwa penulisan kerja laboratorium dengan laporan laboratorium yang diformat SWH dapat meningkatkan kemampuan pelajar dalam argumentasi ilmiah mereka.How to Cite : Firmansyah, R. A., Kumala, L. H. (2018). The Ability of Students’scientific Argumentation of Acid-Base and Buffer Solution Through Science Writing Heuristic (SWH). TARBIYA: Journal of Education in Muslim Society, 5(2), 166-177. doi:10.15408/tjems.v5i2.10412.